DIVERSION NOT DETENTION FOR YOUNG OFFENDERS IN NIGERIA: AN URGENT CALL TO RETHINK - Diyoke, Michael Chika; Ogboke, Eberechukwu Odichinma (African Journal of Social and Behavioural Sciences, 2024)
The paper examined the prevailing approach to detaining young offenders in Nigeria. Specifically, the objectives of the study were to evaluate the existing methods of detaining young offenders and their effectiveness in terms of rehabilitation and reintegration into society and to examine the negative impacts of current detention approaches on young offenders. The methodology was based on the review of published articles, books and journals and an exemplar case study technique in order to draw a conclusion on the contemporary issues of diversion and detention in Nigeria. Findings from the paper revealed that the current detention approach exacerbates criminal behaviour, impedes rehabilitation opportunities, and fails to address the root causes of youth crime. Factors such as poverty, dysfunctional families, limited access to resources, and a lack of rehabilitative efforts contribute to a cycle of criminal behaviour among young offenders. The study further revealed that to address these issues, diversion programs are proposed as a promising alternative. Successful examples from various countries, such as restorative justice programs in New Zealand, youth offender panels in England and Wales, drug treatment courts in Canada, and juvenile mental health courts in the United States, provide valuable insights for Nigeria. The paper concludes by recommending the strengthening of legislation to explicitly recognize diversion programs as alternatives to traditional criminal justice processes, which would involve establishing eligibility criteria, defining procedures, and implementing safeguards to protect the rights of participants.